The role of Free Cash Flow as a moderating factor in Intellectual Capital Disclosure which is influenced by the Audit Committee and Audit Quality - Surjadi, Merna; Bangun, Nurainun; Widiayana, Widiayana (Dinasti Publisher, 2024)
Intellectual Capital is all knowledge assets that can be differentiated between stakeholder resources and structural resources. This research aims to analyze the influence of the audit committee and audit quality on intellectual capital disclosure and to analyze whether there is a role for free cash flow as a moderating variable in the influence of the audit committee and audit quality on the company's intellectual capital disclosure. This research uses a population of banking companies listed on the Indonesian capital market (BEI). This research sample consists of 30 banking companies whose data can be used for this research with a research period of 5 (five) years, from 2017-2022 where the total analysis data units that can be processed for this research amount to a total of 150 analysis data units. This existing data was processed with the help of statistical tools SPSS software version 26.00. By using multiple regression analysis to test the hypothesis in this research, the following research results can be produced: (1) The Audit Committee has a significant effect on Intellectual Capital disclosure; (2) Audit quality has a significant effect on Intellectual Capital disclosure; (3) Free Cash Flow moderates the relationship between the Audit Committee regarding Intellectual Capital disclosure; (4) Free Cash Flow moderates the relationship between Audit Quality and Intellectual Capital disclosure. Limitations in the research include that the audit committee is only assessed from the number of committees in the company so that in further research the audit committee can be assessed from the number of meetings held. Further research is recommended to expand sectors other than banking to be used as research samples, such as the energy sector or other sectors in the Indonesian capital market.